2021
DOI: 10.7150/ijms.46811
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of CAR-T Therapy for Relapse or Refractory Multiple Myeloma: A systematic review and meta-analysis

Abstract: Background: Multiple myeloma (MM) is incurable in spite of recent treatment improvements, highlighting the development of new therapies. Chimeric antigen receptor (CAR) T-cell therapy has dramatically changed the therapeutic effectiveness in high-risk B-cell malignancies. For relapsed/refractory multiple myeloma (RRMM), preclinical evaluations of CAR-T therapy have shown promising efficacy, thus various active clinical trials are under way. Herein, we conducted this review to summarize efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 62 publications
(47 reference statements)
0
15
2
Order By: Relevance
“…• No data are available about dose modifications of promising and effective treatment as CAR-T cells [122][123][124] therapy, bi-specific antibodies [125][126][127], and other agents as Venetoclax [128][129][130], Melfuflen [131][132][133], and Iberdomide [134,135] in case of renal impairment, and particularly dialysis-dependence.…”
Section: Medical Therapymentioning
confidence: 99%
“…• No data are available about dose modifications of promising and effective treatment as CAR-T cells [122][123][124] therapy, bi-specific antibodies [125][126][127], and other agents as Venetoclax [128][129][130], Melfuflen [131][132][133], and Iberdomide [134,135] in case of renal impairment, and particularly dialysis-dependence.…”
Section: Medical Therapymentioning
confidence: 99%
“…Emerging studies support the good effectiveness and safety of CAR-T therapy on the population with relapsed / refractory MM [5][6]. A meta-analysis reported that the survival rate of MM patients within 12 months after CAR-T therapy reached to 78% [7]. Moreover, Guo et al found that among ve patients with relapsed/refractory MM who received CD138z CAR-T therapy, four patients were in stable disease longer than three months, one patient with advanced plasma cell leukemia had a reduction of the myeloma cells in her peripheral blood (from 10.5-3%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, < 20% of lung cancer patients and < 45% of patients with malignant melanoma respond to PDL1 inhibitors 36,37 . Similarly, recent reviews indicate that objective and complete response rates to CAR T cell therapy vary widely from study to study [38][39][40] . Given the large number of nonresponding patients, and the costs and toxicities associated with the above immunotherapies, a biomarker that could effectively predict treatment outcome prior to treatment or early during treatment would be highly valued.…”
Section: Introductionmentioning
confidence: 99%